Assessment of Categories of Personnel in Private University Libraries in South East Nigeria Based on LRCN Minimum Standards and Guidelines - Okechukwu, Ngozi Njideka; Echedom, Anthonia Ukamaka (Education and Development Research, 2026)
The success of the university libraries is greatly determined by the number of qualified staff available and the categorization of staff as per the regulatory standards. There have however been questions on just how far these libraries are complying with the minimum staffing regulations as required by the Librarians Registration Council of Nigeria (LRCN) especially in the South East where the growth of the private universities has not necessarily been accompanied by a corresponding growth in libraries. The research design adopted is a descriptive survey research design to develop a systematic system of data collection and data description of the private university libraries in South East Nigeria. The research is done on the 14 private universities in the area, through a census method. An observation checklist and structured interview guide based on Librarians standards of Registration Council of Nigeria are used to collect data. The results indicate that the number of staff in the libraries of the private universities in South East Nigeria differs with an average of 59% being the number of professionals librarians out of the total number of the staff, which is beyond the minimum requirement of Librarians Registration Council of Nigeria (LRCN) of 35%. The para-professionals and support staff however contributed to only 41 per cent as opposed to the recommended 65, which means that staff composition is not adhering to expectations. Even though the majority of professional librarians had the appropriate qualifications (primarily BLIS, Master, and PhD), the percentage of LRCN-certified ones was 37.